If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3T + -6 = 6 + -3T Reorder the terms: -6 + 3T = 6 + -3T Solving -6 + 3T = 6 + -3T Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '3T' to each side of the equation. -6 + 3T + 3T = 6 + -3T + 3T Combine like terms: 3T + 3T = 6T -6 + 6T = 6 + -3T + 3T Combine like terms: -3T + 3T = 0 -6 + 6T = 6 + 0 -6 + 6T = 6 Add '6' to each side of the equation. -6 + 6 + 6T = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 6T = 6 + 6 6T = 6 + 6 Combine like terms: 6 + 6 = 12 6T = 12 Divide each side by '6'. T = 2 Simplifying T = 2
| 4x-3y=-29 | | 2x+x+2X=405 | | 7(2b+8)=34b+136 | | -1+2x+6x=-33 | | 32-21=5(6x-4)+2x-1 | | X-5=8x+7 | | 10x^3+20x^2-10x-10=x^3+2x^2-9x-8 | | 14=l*w+2 | | 0.6(5x-15)-9=5.5x | | (m-7)-91=539 | | 10+5(7-6x)=17-16x | | 3x-10y=-77 | | X+(x-12)+(x-9)=135 | | 7x+3(-6x-17)=59 | | 10xy+14x+15y+21= | | (12x-8)0.25+6=23 | | 5x-6z= | | 7(2b+8)= | | 2=r+13x | | x=y^2-5y+20 | | 3(3x-4)=-9x+11 | | (8x^3-4x^2+x)-(2x^3+9x^2-4x)= | | 27-11x=x(-33) | | 6(2-r)=18 | | x-3=390 | | 3z-18=2z | | 50=5x+x+2 | | (X-6)4+35=119 | | 3x^2+3y^2=2 | | ln(7x+1)+ln(2x+1)=0 | | xc+xb+yc+yb= | | x-3x+10=X+4 |